Background factors and female dominance - Mirardi, Asghar; Edalati, Ali; Redzuan, Ma'rof (Canadian Center of Science and Education, 2010)
The aim of this study is examine the relationship between duration of marriage, number of children, years of education and family income with female dominance. The study employed survey design. It was carried out among a sample of 337 married women in Shiraz City, Iran. Hamby Dominance Scale (HDS) was used to measure romantic dominance. The study employed correlations test to determine the relationships between duration of marriage, number of children, years of education and family income with female dominance. The study found that there were not significant relationships between duration of marriage, women education and women age with female dominance. There were significant relationship between number of children and family income with female dominance. The result of Regression Analysis showed that the number of children and family income factors contributed 7.4% in explaining the female dominace.